Silicon-carbon composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202611126803.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-30
AI Technical Summary
然而,上述现有技术仍存在诸多不足:喷墨印刷方式难以实现锂粉在纳米级孔隙中的均匀分散,且预锂化程度不易精确控制;含锂聚合物包覆方式则存在工序复杂、成本较高的问题
(1)本发明通过将锂粒子预先均匀附着于介孔碳材料的孔隙内壁上,实现了锂粒子在介孔碳材料中的均匀分散,为后续硅碳负极的均匀预锂化奠定了基础。锂源前置减少了锂的氧化和活性锂的流失,可通过含锂有机溶液的用量来调节硅碳材料的首次库仑效率。
Smart Images

Figure CN123017920A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery materials technology, and in particular to a silicon-carbon composite material, its preparation method, and its application. Background Technology
[0002] In lithium-ion batteries, the anode material is one of the key factors limiting battery performance. While traditional graphite anode materials have mature processes, low cost, and good performance, their theoretical specific capacity is nearing its limit (372 mAh / g), limiting the potential for energy density optimization in graphite-based lithium batteries. Silicon-based anode materials, with their extremely high theoretical specific capacity (approximately 4200 mAh / g), have become an important research direction in the field of next-generation lithium-ion battery anode materials. However, silicon-based anode materials suffer from severe volume expansion and low initial coulombic efficiency during charge and discharge, significantly hindering their commercial application.
[0003] To address the aforementioned issues, various modification methods for silicon-based anode materials have been developed in this field, including silicon oxidation, nano-sizing, composite formation, porosification, and pre-lithiation. Among these, the pre-lithiation method for preparing silicon-carbon composite materials is considered one of the most promising technological routes for industrialization due to its ability to effectively improve initial coulombic efficiency, reduce expansion, and enhance cycle stability.
[0004] For example, Chinese invention patent CN112072078A uses inkjet printing to print an inert lithium powder dispersion onto a negative electrode for pre-lithiation; Chinese invention patent CN118825229A achieves pre-lithiation by sequentially coating a carbon coating layer and a lithium-containing polymer composite coating layer onto a silicon-carbon material substrate. However, the above-mentioned existing technologies still have many shortcomings: inkjet printing is difficult to achieve uniform dispersion of lithium powder in nanoscale pores, and the degree of pre-lithiation is not easy to control precisely; the lithium-containing polymer coating method has the problems of complex process and high cost. More importantly, the above solutions are all back-end pre-lithiation—that is, lithium replenishment is performed after the silicon-carbon material is prepared. In this mode, lithium elements are mainly distributed on the surface of the material and it is difficult to fully enter the internal pores of the mesoporous carbon material to form effective alloy with the nano-silicon particles, resulting in low pre-lithiation efficiency and insufficient utilization of active lithium. In addition, existing pre-lithiation processes generally have problems such as complex process, poor pre-lithiation uniformity, and difficulty in precisely controlling the degree, which restricts their large-scale application.
[0005] Therefore, there is an urgent need for a silicon-carbon composite material with high pre-lithiation efficiency, uniform lithium distribution, simple and controllable process, and the ability to simultaneously improve the expansion and cycle performance of silicon-based anode materials, as well as its preparation method. Summary of the Invention
[0006] The purpose of this invention is to address the deficiencies of existing technologies by providing a silicon-carbon composite material, its preparation method, and its application. This silicon-carbon composite material, used as the negative electrode of a lithium-ion battery, can improve the initial coulombic efficiency, rate capability, and cycle performance. To achieve the above objectives, the present invention provides a silicon-carbon composite material, the silicon-carbon composite material comprising: Mesoporous carbon materials; Lithium particles are uniformly attached to the inner pore walls of the mesoporous carbon material. Nano-silicon particles are obtained by vapor deposition in the pores of the mesoporous carbon material. Germanium nanoparticles were obtained by vapor deposition in the pores of the mesoporous carbon material. Lithium-silicon alloy particles and / or lithium-germanium alloy particles and / or lithium-silicon-germanium alloy particles are located inside the pores of the mesoporous carbon material; Silicon-germanium alloy particles are located inside the mesoporous carbon material and are generated by in-situ alloying reaction between the nano-silicon particles and the nano-germanium particles at the interface. A carbon coating layer is applied to the outer surface of the mesoporous carbon material. The lithium particles are obtained by vaporizing a lithium-containing organic solution and adsorbing it into the pores of the mesoporous carbon material, followed by pyrolysis. Some of the lithium particles undergo an in-situ alloying reaction with some of the nano-silicon particles and / or some of the nano-germanium particles generated by subsequent vapor deposition to generate lithium-silicon alloy particles and / or lithium-germanium alloy particles and / or lithium-silicon-germanium alloy particles. In the pores of the mesoporous carbon material, nano-silicon layers formed by the aggregation of nano-silicon particles and nano-germanium layers formed by the aggregation of nano-germanium particles are arranged alternately to form a silicon-germanium alternating sandwich structure; silicon-germanium alloy particles are present at the interface between the nano-silicon layers and the nano-germanium layers.
[0007] Preferably, the mesoporous carbon material has a mesoporous rate of 50%-95%; a pore size of 0.2 nm-10 nm; and a pore volume of 0.6 cm³. 3 / g-1.2cm 3 / g; the specific surface area of the mesoporous carbon material is 110m². 2 / g-2000m 2 / g.
[0008] Preferably, the specific surface area of the silicon-carbon composite material is 1 m². 2 / g-10m 2 / g; the particle size D50 of the silicon-carbon composite material is 3μm-15μm.
[0009] Secondly, this application provides a method for preparing a silicon-carbon composite material as described in the first aspect, the method comprising: Step S1: Mix the carbon precursor and the pore-forming agent in a certain proportion, and perform carbonization treatment under a protective atmosphere to obtain a carbonized precursor. Then, remove the residual pore-forming agent and its by-products in the carbonized precursor by acid washing and water washing until the solution is neutral. Finally, dry the precursor to obtain a mesoporous carbon material. Step S2: Lithium metal is placed in an organic solution under a protective atmosphere and stirred continuously until fully dissolved to obtain a lithium-containing organic solution; the organic solution includes an organic solvent and a co-solvent, and during the stirring process, the lithium metal combines with part of the co-solvent to form a lithium-co-solvent complex; Step S3: Place the mesoporous carbon material in the deposition chamber of the deposition furnace, introduce inert gas into the deposition chamber to expel air, heat the deposition furnace to the first deposition temperature, and carry the lithium-containing organic solution into the deposition chamber through the inert carrier gas. The lithium-containing organic solution forms mist droplets. As the organic solvent in the mist droplets evaporates, the lithium-cosolvent complex and the remaining cosolvent in the lithium-containing organic solution are uniformly attached to the inner pore wall of the mesoporous carbon material. Step S4: Inert gas is introduced into the deposition chamber for purging to remove residual organic solvents and their pyrolysis products, as well as the remaining co-solvent. Subsequently, the deposition furnace is heated to the second deposition temperature, causing the lithium-co-solvent complex adhering to the inner wall of the pores to thermally decompose and release lithium particles. Then, the chamber temperature is maintained at the second deposition temperature, and silicon source gas is introduced into the deposition chamber through an inert carrier gas and kept at the temperature, so that the silicon generated by the pyrolysis of the silicon source gas is deposited in the pores of the mesoporous carbon material, growing to form nano-silicon particles. At the same time, some of the nano-silicon particles undergo an in-situ alloying reaction with some of the lithium particles to generate lithium-silicon alloy particles. Step S5: Adjust the temperature of the deposition furnace to the third deposition temperature, introduce germanium source gas into the deposition chamber using an inert carrier gas and keep it at the temperature, so that the germanium produced by the pyrolysis of the germanium source gas is deposited in the pores of the mesoporous carbon material, growing to form nano-germanium particles; simultaneously, some of the nano-germanium particles undergo an in-situ alloying reaction with some of the lithium particles to generate lithium-germanium alloy particles; furthermore, some of the nano-germanium particles undergo an in-situ alloying reaction with the lithium-silicon alloy particles to generate lithium-silicon-germanium alloy particles. Step S6: Repeat steps S4 and S5 for a total of N times, and then execute step S4 one more time. In the pores of the mesoporous carbon material, a silicon-germanium alternating sandwich structure is formed, in which nano-silicon layers formed by the aggregation of nano-silicon particles and nano-germanium layers formed by the aggregation of nano-germanium particles are alternately arranged, and silicon-germanium alloy particles are formed at the interface between the nano-silicon layers and the nano-germanium layers, thus obtaining the precursor material; wherein, N≥2. Step S7: Carbon coating treatment is performed on the precursor material to form a carbon coating layer on the outer surface of the precursor material, thereby obtaining a silicon-carbon composite material.
[0010] Preferably, the carbon precursor comprises a carbon-containing polymer, which includes one or more of glucose, sucrose, starch, polyvinylpyrrolidone, polyvinylidene fluoride, phenolic resin, polyvinyl chloride, or cellulose. The pore-forming agent includes one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, or sodium sulfate; The lithium metal includes one or more of lithium sheets, lithium blocks, or lithium powder; The organic solvent includes one or more of 1,2-dimethoxyethane, tetrahydrofuran, diethyl ether, dioxolane, dimethyl sulfoxide, or dimethylformamide; the co-solvent is an aromatic hydrocarbon compound, including one or more of biphenyl or naphthalene. The protective atmosphere includes one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The inert gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The inert carrier gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The silicon source gas includes one or more of silanes or chlorosilanes; The germanium source gas includes one or more of germane, digermane, or propargane. The carbon source gas includes one or more of methane, ethane, propane, or acetylene.
[0011] Preferably, the mass ratio of the carbon precursor to the pore-forming agent is 1:1 to 1:5; The mass ratio of the mesoporous carbon material to the lithium-containing organic solution is 100:1-100:5; The lithium concentration in the lithium-containing organic solution is 0.1wt%-0.3wt%; The flow rate of the lithium-containing organic solution is 10 mL / min-40 mL / min; The flow rate of the inert gas is 2L / min-10L / min; The flow rate of the inert carrier gas is 50L / min-125L / min; The flow rate of the silicon source gas is 4L / min-20L / min; The flow rate of the germanium source gas is 4L / min-20L / min.
[0012] Preferably, the carbonization temperature is 700℃-1300℃, and the carbonization time is 1h-4h; The drying temperature is 50℃-130℃, and the drying time is 3h-15h; The first deposition temperature is 80℃-360℃, and the holding time is 200min-800min; The second deposition temperature is 400℃-500℃, and the holding time is 1h-36h; The third deposition temperature is 300℃-400℃, and the holding time is 1h-36h.
[0013] Preferably, the carbon coating treatment includes: The precursor material is placed in a reactor, heated to 500℃-750℃ under a protective atmosphere, and then subjected to chemical vapor deposition (CVD) for 1-4 hours by introducing a carbon source gas; or... The precursor material is immersed in a carbon precursor solution for 3-8 hours, then removed and dried, and then carbonized at 500-750°C for 1-4 hours under a protective atmosphere.
[0014] Thirdly, this application provides a negative electrode sheet, which includes the silicon-carbon negative electrode material described in the first aspect above, or the silicon-carbon negative electrode material prepared by the preparation method described in the second aspect above.
[0015] Fourthly, this application provides an energy storage device, the energy storage device comprising: for a lithium-ion battery or a lithium-ion capacitor; The energy storage device includes the silicon-carbon anode material described in the first aspect above, or the silicon-carbon anode material prepared by the preparation method described in the second aspect above, or the silicon-carbon anode material described in the third aspect above.
[0016] The silicon-carbon composite material provided in this invention, by placing a pre-lithiation process before silicon deposition in the mesoporous carbon material, first uniformly introduces a lithium-containing organic solution in atomized form into the pores of the mesoporous carbon, allowing lithium particles to be uniformly attached to the interior of the carbon pores beforehand. Subsequently, silicon and germanium are introduced sequentially through vapor deposition, allowing the newly generated nano-silicon / nano-germanium particles to directly undergo an in-situ alloying reaction with the pre-placed lithium particles within the pores, achieving uniform distribution and efficient utilization of lithium at the molecular scale. Based on this, by repeatedly and alternately depositing silicon and germanium in the vapor phase, a silicon-germanium alternating sandwich structure is formed. This not only effectively refines the silicon grain size and buffers volume expansion, but also utilizes the high electronic conductivity of germanium to improve the rate performance of the material. Simultaneously, the silicon-germanium alloy particles at the interface between the nano-silicon and nano-germanium layers enhance the interfacial bonding stability of the sandwich structure, effectively preventing interlayer delamination caused by silicon volume expansion during cycling, thereby improving the cycling stability of the material. Furthermore, the carbon coating layer on the outermost surface reduces irreversible capacity loss. The silicon-carbon composite material provided in this application can effectively improve the initial coulombic efficiency, rate performance, and cycle stability when applied to the negative electrode of a lithium-ion battery. Attached Figure Description
[0017] Figure 1 A flowchart illustrating the preparation method of silicon-carbon composite material provided in this embodiment of the invention. Detailed Implementation
[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0019] The reagents and materials used in the following examples and comparative examples are all commercially available conventional reagent products, or can be prepared by conventional methods. Where specific experimental steps or conditions are not specified in the examples, they were performed according to conventional experimental steps and conditions in the art. Unless otherwise specified, all equipment used is conventional equipment currently available in the art.
[0020] It should be noted that the particle size D50 of silicon-carbon composite materials refers to the median particle size of silicon-carbon composite materials, while the particle size D50 of mesoporous carbon materials refers to the median particle size of mesoporous carbon materials, which can be the median value sorted by volume, mass, or quantity. In this example, it is the median particle size sorted by volume, representing the particle size of the material that accounts for 50% of the volume distribution. Particle size D50 is a well-known meaning in the art. The particle size D50 of the materials provided in the embodiments of the present invention can be determined by instruments and conventional methods known in the art. Specifically, in all embodiments of the present invention, the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK, is used to determine the particle size D50.
[0021] In this invention, the pore size of mesoporous carbon materials refers to the diameter of the internal pores within the mesoporous carbon material, a meaning known in the art. The pore structure parameters (specific surface area of the silicon-carbon composite material, and specific surface area, pore size, and mesoporosity of the mesoporous carbon material) provided in the embodiments of this invention can be determined using instruments and conventional methods known in the art. Specifically, this invention uses a nitrogen adsorption-desorption method to characterize the pore structure of the sample, and the testing instrument is a BSD-660S specific surface area analyzer. During testing, the sample is degassed under vacuum, and the nitrogen adsorption-desorption isotherm is measured; the specific surface area of the sample is calculated based on BET theory; the pore volume and pore size distribution of the sample are obtained by analyzing the desorption curve based on the BJH model; finally, the mesoporous pore volume in the range of 2nm-50nm is obtained by integrating the pore size distribution data, and the mesoporosity of the sample is calculated by combining the sample mass and framework density.
[0022] The contents of lithium, silicon, and germanium in the samples were determined using inductively coupled plasma optical emission spectrometry (ICP-OES). Before testing, the samples were microwave-digested, and standard solutions were prepared to establish a standard curve. The mass percentage of each element was then quantitatively calculated using the standard curve method.
[0023] Thickness testing method: The cross-section of the material was observed using a transmission electron microscope (accelerating voltage 200kV). The thickness of the film was measured at 20 randomly selected locations, and the arithmetic mean was taken as the thickness value of the film.
[0024] This invention provides a silicon-carbon composite material, which comprises: Mesoporous carbon materials; Lithium particles are uniformly attached to the inner pore walls of the mesoporous carbon material. Nano-silicon particles are obtained by growing in the pores of mesoporous carbon materials via vapor deposition. Germanium nanoparticles were obtained by vapor deposition in the pores of mesoporous carbon materials. Lithium-silicon alloy particles and / or lithium-germanium alloy particles and / or lithium-silicon-germanium alloy particles are located inside the pores of the mesoporous carbon material; Silicon-germanium alloy particles, located inside mesoporous carbon materials, are generated by in-situ alloying reaction of nano-silicon particles and nano-germanium particles at the interface. A carbon coating layer, which coats the outer surface of the mesoporous carbon material; The lithium particles are obtained by vaporizing a lithium-containing organic solution and adsorbing it into the pores of a mesoporous carbon material, followed by pyrolysis. Some of the lithium particles undergo in-situ alloying reactions with some nano-silicon particles and / or some nano-germanium particles generated by subsequent vapor deposition to generate lithium-silicon alloy particles and / or lithium-germanium alloy particles and / or lithium-silicon-germanium alloy particles. In the pores of mesoporous carbon materials, nano-silicon layers formed by the aggregation of nano-silicon particles and nano-germanium layers formed by the aggregation of nano-germanium particles are arranged alternately to form a silicon-germanium alternating sandwich structure; silicon-germanium alloy particles exist at the interface between the nano-silicon layers and the nano-germanium layers.
[0025] The mesoporous carbon material has a mesoporosity of 50%-95%; a pore size of 0.2 nm-10 nm; and a pore volume of 0.6 cm³. 3 / g-1.2cm 3 / g; The specific surface area of the mesoporous carbon material is 110m². 2 / g-2000m 2 / g.
[0026] The specific surface area of silicon-carbon composite material is 1 m². 2 / g-10m 2 / g; the particle size D50 of the silicon-carbon composite material is 3μm-15μm.
[0027] The mass of lithium element accounts for 0.5wt%-1.5wt% of the total mass of silicon-carbon composite material; among which, lithium element includes lithium element in lithium particles, lithium-silicon alloy particles, lithium-germanium alloy particles and lithium-silicon-germanium alloy particles.
[0028] The mass of silicon element accounts for 27wt%-70wt% of the total mass of silicon-carbon composite materials; among which, silicon element includes silicon element in nano-silicon particles, lithium-silicon alloy particles, silicon-germanium alloy particles and lithium-silicon-germanium alloy particles.
[0029] Germanium accounts for 2wt%-5wt% of the total mass of silicon-carbon composite materials; among which, germanium includes germanium in nano-germanium particles, lithium-germanium alloy particles, silicon-germanium alloy particles and lithium-silicon-germanium alloy particles.
[0030] Mesoporous carbon materials account for 25.5 wt% to 68.5 wt% of the total mass of silicon-carbon composite materials.
[0031] The carbon coating layer accounts for 2wt%-10wt% of the total mass of the silicon-carbon composite material.
[0032] The silicon-carbon composite material provided in this invention, by placing a pre-lithiation process before silicon deposition in the mesoporous carbon material, first uniformly introduces a lithium-containing organic solution in atomized form into the pores of the mesoporous carbon, allowing lithium particles to be uniformly attached to the interior of the carbon pores beforehand. Subsequently, silicon and germanium are introduced sequentially through vapor deposition, allowing the newly generated nano-silicon / nano-germanium particles to directly undergo an in-situ alloying reaction with the pre-placed lithium particles within the pores, achieving uniform distribution and efficient utilization of lithium at the molecular scale. Based on this, by repeatedly and alternately depositing silicon and germanium in the vapor phase, a silicon-germanium alternating sandwich structure is formed. This not only effectively refines the silicon grain size and buffers volume expansion, but also utilizes the high electronic conductivity of germanium to improve the rate performance of the material. Simultaneously, the silicon-germanium alloy particles at the interface between the nano-silicon and nano-germanium layers enhance the interfacial bonding stability of the sandwich structure, effectively preventing interlayer delamination caused by silicon volume expansion during cycling, thereby improving the cycling stability of the material. Furthermore, the carbon coating layer on the outermost surface reduces irreversible capacity loss. The silicon-carbon composite material provided in this application can effectively improve the initial coulombic efficiency, rate performance, and cycle stability when applied to the negative electrode of a lithium-ion battery.
[0033] In addition, this invention also provides a method for preparing the above-mentioned silicon-carbon composite material, the main steps of which are as follows: Figure 1 As shown, it includes the following steps: Step S1: Mix the carbon precursor and pore-forming agent in a certain proportion, and perform carbonization treatment under a protective atmosphere to obtain a carbonized precursor. Then, remove the residual pore-forming agent and its by-products in the carbonized precursor by acid washing and water washing until the solution is neutral. Finally, dry the precursor to obtain the mesoporous carbon material.
[0034] In this step, the carbon precursor comprises a carbon-containing polymer, which includes one or more of glucose, sucrose, starch, polyvinylpyrrolidone, polyvinylidene fluoride, phenolic resin, polyvinyl chloride, or cellulose. The pore-forming agent includes one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, and sodium sulfate. The mass ratio of the carbon precursor to the pore-forming agent is controlled between 1:1 and 1:5.
[0035] Mechanical mixing is employed for 1-5 hours to ensure uniform mixing of the carbon precursor and the pore-forming agent. The mixture is placed in a tube furnace or muffle furnace, and argon, nitrogen, or helium is introduced as a protective atmosphere to remove oxygen from the furnace. The temperature is then increased to 700-1300℃ at a rate of 3-10℃ / min and held for 1-4 hours for high-temperature carbonization. During high-temperature carbonization, the carbon precursor carbonizes to form a carbon framework, while the pore-forming agent acts as an activating etchant to etch the carbon framework, creating abundant pores, thus obtaining the carbonized precursor.
[0036] After carbonization, the obtained carbonized precursor was added to an inorganic acid solution for acid washing to remove residual pore-forming agent and its byproducts. It was then repeatedly washed with deionized water until the pH of the filtrate was neutral. Finally, the washed product was dried in an oven at 50℃-130℃ for 3-15 hours to obtain mesoporous carbon material. This mesoporous carbon material has a mesoporosity of 50%-95%, a pore size of 0.2nm-20nm, and a pore volume of 0.6cm³. 3 / g-1.0cm 3 / g, specific surface area is 110m² 2 / g-2000m 2 / g provides ample internal space for subsequent lithium, silicon and germanium deposition.
[0037] The protective atmosphere includes one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The gas flow rate of the protective atmosphere is 2 L / min to 10 L / min.
[0038] The inorganic acid solution includes one or more of hydrochloric acid or sulfuric acid, wherein the concentration of the inorganic acid solution is 15wt%-25wt%, and the amount used can be adjusted according to actual needs.
[0039] It should be noted that, as needed, the washed and dried product can be pulverized by air jet milling or ball milling to obtain finely granulated mesoporous carbon materials.
[0040] Step S2: Lithium metal is placed in an organic solution under a protective atmosphere and stirred continuously until fully dissolved to obtain a lithium-containing organic solution. The organic solution includes an organic solvent and a co-solvent. During the stirring process, lithium metal combines with part of the co-solvent to form a lithium-co-solvent complex.
[0041] The purpose of this step is to prepare an organic solution rich in active lithium. Specifically, to prevent lithium metal oxidation or reaction with moisture in the air, this step is carried out in a glove box under a protective atmosphere. A co-solvent is added to the organic solvent and stirred until completely dissolved to obtain an organic solution. Then, lithium metal is added to this organic solution, and stirring is continued at room temperature for 6-20 hours until the lithium metal is completely dissolved, resulting in a lithium-containing organic solution. In this lithium-containing organic solution, the lithium concentration is 0.1wt%-0.3wt%, and the co-solvent concentration is 10wt%-30wt%.
[0042] The protective atmosphere includes one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm.
[0043] The organic solvent includes one or more of 1,2-dimethoxyethane, tetrahydrofuran, diethyl ether, dioxolane, dimethyl sulfoxide, or dimethylformamide; the co-solvent is an aromatic hydrocarbon compound, including one or more of biphenyl or naphthalene. During stirring, lithium metal dissolves in the organic solvent under the action of the co-solvent, forming a lithium-containing organic solution. Specifically, lithium metal and the co-solvent form a lithium-co-solvent complex that dissolves in the organic solvent, meaning that lithium exists in the solution as a soluble complex. The lithium-co-solvent complex is stable at room temperature and exhibits good fluidity, allowing it to be transported into the pores of the mesoporous carbon material via gas-phase transport.
[0044] Step S3: Place the mesoporous carbon material in the deposition chamber of the deposition furnace, introduce inert gas into the deposition chamber to expel air, heat the deposition furnace to the first deposition temperature, and introduce the lithium-containing organic solution into the deposition chamber through the inert carrier gas. The lithium-containing organic solution forms mist droplets. As the organic solvent in the mist droplets evaporates, the lithium-cosolvent complex and the remaining cosolvent in the lithium-containing organic solution are uniformly attached to the inner pore wall of the mesoporous carbon material.
[0045] Mesoporous carbon material is placed in the deposition chamber of a deposition furnace, and inert gas is introduced at a flow rate of 2-10 L / min to purge the air from the chamber. The furnace is then heated to 80-360°C at a rate of 1-10°C / min and held at this temperature for 200-800 min. A lithium-containing organic solution is then introduced into the deposition chamber at a flow rate of 10-40 mL / min using an inert carrier gas. Under the influence of the high temperature and high-speed carrier gas flow, the lithium-containing organic solution forms atomized droplets. Due to the large specific surface area of the atomized droplets, the internal organic solvent rapidly evaporates and is thermally decomposed and removed, while the thermally stable lithium-co-solvent complex and the remaining co-solvent that has not bonded to lithium metal are uniformly adhered to the pore walls of the mesoporous carbon material. This step achieves a uniform distribution of lithium particles within the pores of the mesoporous carbon material, avoiding the uneven distribution caused by traditional surface coating. The mass ratio of mesoporous carbon material to lithium-containing organic solution is 100:1-100:5.
[0046] The inert gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in nitrogen is less than 5 ppm. The inert gas flow rate is 2 L / min to 10 L / min.
[0047] The inert carrier gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in nitrogen is less than 5 ppm. The flow rate of the inert carrier gas is 50 L / min to 125 L / min.
[0048] Step S4: Inert gas is introduced into the deposition chamber for purging to remove residual organic solvents and their pyrolysis products, as well as the remaining co-solvent. Subsequently, the deposition furnace is heated to the second deposition temperature, causing the lithium-co-solvent complex attached to the inner wall of the pores to thermally decompose and release lithium particles. Then, the chamber temperature is maintained at the second deposition temperature, and silicon source gas is introduced into the deposition chamber through an inert carrier gas and kept at the temperature, so that the silicon generated by the pyrolysis of the silicon source gas is deposited in the pores of the mesoporous carbon material, growing to form nano-silicon particles. At the same time, some nano-silicon particles undergo in-situ alloying reactions with some lithium particles to generate lithium-silicon alloy particles.
[0049] Stop introducing the lithium-containing organic solution and continue introducing the protective gas to purge the residual organic solvent and its pyrolysis products, as well as the remaining co-solvent, from the chamber to prevent interference with subsequent vapor deposition.
[0050] Subsequently, the temperature of the deposition furnace is raised to the second deposition temperature of 400℃-500℃. At this temperature, the lithium-cosolvent complex attached to the inside of the pores undergoes pyrolysis, releasing highly active lithium particles, which include lithium atoms or lithium metal clusters.
[0051] Next, silicon source gas is introduced into the deposition chamber via an inert carrier gas and held at that temperature for 1-36 hours. At high temperatures, the silicon source gas pyrolyzes to generate silicon atoms; for example, in silane: SiH4 → Si + 2H2. Driven by a concentration gradient, silicon atoms diffuse into the pores of the mesoporous carbon material and nucleate and grow on the inner walls of the pores, forming nano-silicon particles. Because the newly formed nano-silicon particles are in a highly reactive state, they undergo an in-situ alloying reaction with lithium particles attached to the inside of the pores, generating lithium-silicon alloy particles.
[0052] This step ensures uniform doping of nano-silicon particles within the pores of the mesoporous carbon material, effectively improving the material's initial coulombic efficiency and alleviating the volume expansion stress of silicon.
[0053] The inert gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in nitrogen is less than 5 ppm. The inert gas flow rate is 2 L / min to 10 L / min.
[0054] The inert carrier gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in nitrogen is less than 5 ppm. The flow rate of the inert carrier gas is 50 L / min to 125 L / min.
[0055] The silicon source gas includes one or more of silanes or chlorosilanes; wherein the silane includes one or more of methylsilane, dimethylsilane, or bissilane; preferably, the silicon source gas is methylsilane. The silicon source gas flow rate is 4 L / min-20 L / min.
[0056] In step S5, the temperature of the deposition furnace is adjusted to the third deposition temperature. The germanium source gas is introduced into the deposition chamber through an inert carrier gas and kept at the temperature. The germanium produced by the pyrolysis of the germanium source gas is deposited in the pores of the mesoporous carbon material, growing to form nano-germanium particles. At the same time, some nano-germanium particles undergo an in-situ alloying reaction with some lithium particles to generate lithium-germanium alloy particles. Furthermore, some nano-germanium particles undergo a further in-situ alloying reaction with lithium-silicon alloy particles to generate lithium-silicon-germanium alloy particles.
[0057] After silicon deposition, the furnace temperature is adjusted to the third deposition temperature of 300℃-400℃. At this temperature, sufficient decomposition of the germanium source gas is ensured while excessive agglomeration of the deposited lithium-silicon alloy particles is avoided. The cooling rate is 1℃ / min-10℃ / min.
[0058] Germanium source gas is introduced into the deposition chamber using an inert carrier gas, with the flow rate controlled at 4 L / min–20 L / min, and held at this temperature for 1–36 hours. At high temperature, the germanium source gas pyrolyzes to generate germanium atoms; for example, in germanane: GeH4 → Ge + 2H2. The generated germanium atoms are deposited on the surface of a nano-silicon layer formed by the aggregation of nano-silicon particles, forming nano-germanium particles. During this process, the following reactions may occur: The remaining lithium particles react with some of the nano-germanium particles to form lithium-germanium alloy particles, and / or, some of the nano-germanium particles react with existing lithium-silicon alloy particles at the interface to form lithium-silicon-germanium alloy particles, and / or, some of the nano-germanium particles react directly with nano-silicon particles at the interface to form silicon-germanium alloy particles.
[0059] The introduction of germanium, with its high conductivity, improves the rate performance of the material.
[0060] The inert carrier gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in nitrogen is less than 5 ppm. The flow rate of the inert carrier gas is 50 L / min to 125 L / min.
[0061] The germanium source gas includes one or more of germanane, digermanane, or propargane; preferably, the germanium source gas is germanane. The flow rate of the germanium source gas is 4 L / min to 20 L / min.
[0062] Step S6: Repeat steps S4 and S5 for a total of N times, and then execute step S4 one more time. In the pores of the mesoporous carbon material, a silicon-germanium alternating sandwich structure is formed, in which nano-silicon layers formed by the aggregation of nano-silicon particles and nano-germanium layers formed by the aggregation of nano-germanium particles are alternately arranged, and silicon-germanium alloy particles are formed at the interface between the nano-silicon layers and the nano-germanium layers, thus obtaining the precursor material; wherein, N≥2.
[0063] To construct a silicon-germanium alternating sandwich structure, this step involves controlled cycling of silicon and germanium deposition, with alternating introduction of silicon and germanium source gases to form a multilayered stacked structure of nano-silicon / nano-germanium layers within the pores of the mesoporous carbon material. At the interface between the nano-silicon and nano-germanium layers, an extremely thin silicon-germanium alloy transition layer is formed in situ due to interatomic diffusion. This sandwich structure not only effectively restricts the size of the silicon grains but also enhances the interlayer bonding force through the silicon-germanium alloy layer formed by the aggregation of silicon-germanium alloy particles, thereby significantly improving the cycling stability of the material.
[0064] Specifically, the number of iterations is set, for example, N is 2-5. First, "step S4 + step S5" is repeated N times. To ensure that the outermost layer of the entire sandwich structure is a nano-silicon layer, step S4 is then executed one more time. Finally, an alternating sandwich structure of "silicon-germanium-silicon-germanium-...-silicon" is formed. Taking N=3 as an example, the sandwich structure is Si-Ge-Si-Ge-Si-Ge-Si.
[0065] Step S7: Carbon coating treatment is performed on the precursor material to form a carbon coating layer on the outer surface of the precursor material, thereby obtaining a silicon-carbon composite material.
[0066] The present invention can employ, but is not limited to, the following two methods to perform carbon coating treatment on precursor materials: (1) Chemical vapor deposition (CVD) The precursor material is placed in a tube furnace or rotary furnace, and heated to 500℃-750℃ at a rate of 3℃ / min-10℃ / min under a protective atmosphere. A mixture of carbon source gas and inert carrier gas (volume ratio 1:1-1:3) is introduced, and CVD treatment is carried out for 1h-4h.
[0067] The protective atmosphere includes one or more of argon, nitrogen, or helium, with the oxygen content in the nitrogen being less than 5 ppm. The carbon source gas includes one or more of methane, acetylene, or propylene. The heating rate is 3℃ / min–10℃ / min. The inert carrier gas includes one or more of argon, nitrogen, or helium; with the oxygen content in the nitrogen being less than 5 ppm.
[0068] (2) Impregnation-carbonization method The precursor material is immersed in a carbon-coated precursor solution for 3-8 hours, then removed and dried, and then carbonized at 500℃-750℃ for 1-4 hours under a protective atmosphere to form a carbon coating layer.
[0069] The protective atmosphere includes one or more of argon, nitrogen, or helium, with the oxygen content in the nitrogen being less than 5 ppm. The coated carbon precursor is specifically an oxygen-containing carbon precursor, including one or more of sucrose, glucose, or phenolic resin. The concentration of the coated carbon precursor solution is adjusted according to actual needs, for example, from 5 wt% to 30 wt%.
[0070] It should be noted that, in this invention, the protective atmosphere refers to the atmospheric environment provided to prevent the material from being oxidized at high temperatures; the inert gas refers to the purge gas used to replace the air in the reaction chamber; and the inert carrier gas refers to the transport gas used to carry and transport the lithium-containing organic solution, silicon source gas, germanium source gas, or carbon source gas into the deposition chamber. The protective atmosphere, inert gas, and inert carrier gas can be independently selected from one or more of argon, nitrogen, or helium, and the types of the three gases can be the same or different from each other.
[0071] The method for preparing silicon-carbon composite materials provided in this invention has the following advantages over the prior art: (1) This invention achieves uniform dispersion of lithium particles in mesoporous carbon materials by pre-attaching lithium particles uniformly to the inner pore walls of the mesoporous carbon materials, laying the foundation for uniform pre-lithiation of silicon-carbon anodes. Pre-positioning the lithium source reduces lithium oxidation and loss of active lithium, and the initial coulombic efficiency of silicon-carbon materials can be adjusted by the amount of lithium-containing organic solution used.
[0072] (2) The present invention forms a silicon-germanium alternating sandwich structure by sequentially vapor-depositing silicon and germanium in the pores of mesoporous carbon material, which reduces the size of silicon grains and improves the expansion performance of the material; at the same time, germanium has a high electronic conductivity, which is beneficial to improving the rate performance of the material.
[0073] (3) In this invention, some lithium particles undergo an in-situ alloying reaction with nano-silicon and / or nano-germanium generated by subsequent vapor deposition to generate lithium-silicon alloy, lithium-germanium alloy and / or lithium-silicon-germanium alloy particles, thereby achieving uniform distribution and efficient utilization of lithium at the atomic level and further improving the first coulombic efficiency of the material.
[0074] (4) By forming a carbon coating layer on the outermost surface of the mesoporous carbon material, the present invention further suppresses the volume expansion of silicon, reduces irreversible capacity loss, and improves the cycling stability of the material.
[0075] (5) The present invention completes the pre-lithiation operation and vapor deposition in the same process, which makes the preparation process simple and controllable, low in cost, and conducive to commercial promotion and application.
[0076] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0077] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0078] To better understand the technical solution provided by the present invention, the preparation process and characteristics of the silicon-carbon composite material provided by the present invention are illustrated below with several specific examples.
[0079] Example 1 This embodiment 1 provides a preparation process for a silicon-carbon composite material, the specific process of which is as follows: Step S1: 300g of cellulose and 100g of potassium hydroxide are mechanically mixed for 3 hours, then placed in a muffle furnace. Nitrogen gas is introduced to remove oxygen from the muffle furnace, and the temperature is raised to 800℃ at a rate of 5℃ / min. The mixture is then held at this temperature for 4 hours under a nitrogen atmosphere to obtain a carbonized precursor. The weight of the carbonized precursor is weighed, and double the weight of 20% hydrochloric acid is added to remove residual potassium hydroxide. The precursor is then washed with a large amount of water until neutral. The washed carbonized precursor is then placed in an oven to dry at 100℃ for 10 hours. After air jet milling, a mesoporous carbon material with a D50 of 10μm is obtained.
[0080] In step S2, 1.5 kg of biphenyl and 18 kg of 1,2-dimethoxyethane are stirred and mixed for 2 hours. Then, under argon protection, 100 g of lithium sheet is added and stirred continuously for 12 hours until the lithium sheet is fully dissolved to obtain a lithium-containing organic solution.
[0081] Step S3: Place the mesoporous carbon material in the deposition chamber of the deposition furnace, introduce argon gas into the deposition chamber to purge air, raise the temperature of the deposition furnace to 280°C, and use argon gas to carry the lithium-containing organic solution into the deposition furnace chamber. Maintain this temperature for 6 hours. The process is considered complete when all the lithium-containing organic solution has been introduced. The inert gas argon flow rate is 8 L / min, the inert carrier gas argon flow rate is 100 L / min, and the lithium-containing organic solution introduction rate is 50 mL / min.
[0082] In step S4, argon gas is introduced into the deposition chamber for purging. Then, the temperature of the deposition furnace is raised to 440℃, and silane is introduced into the deposition chamber via the argon gas. The chamber is held at this temperature for 2 hours, allowing the silicon produced by the pyrolysis of silane to be uniformly deposited in the pores of the mesoporous carbon material. The flow rate of the inert argon gas is 8 L / min, the flow rate of the inert carrier argon gas is 56 L / min, and the flow rate of the silane is 4 L / min.
[0083] In step S5, the temperature of the deposition furnace is adjusted to 340℃, and germane is introduced into the deposition chamber using argon gas. The chamber is held at this temperature for 0.5 hours to allow the germanium produced by the pyrolysis of germane to be uniformly deposited in the pores of the mesoporous carbon material. The inert carrier gas argon has a flow rate of 56 L / min, and the germane gas flow rate is 4 L / min.
[0084] Step S6: Repeat steps S4 and S5 three times, and then execute step S4 one more time. Specifically, execute step S4 → step S5 → step S4 → step S5 → step S4 → step S5 → step S4 to obtain the precursor material.
[0085] In step S7, the temperature of the deposition furnace is raised to 580℃ under an argon atmosphere. Then, propylene with a flow rate of 1L / min is introduced along with the argon gas, and the temperature is maintained for 1 hour to form a carbon coating layer on the outer surface of the precursor material, ultimately obtaining a silicon-carbon composite material. The inert carrier gas argon has a flow rate of 50L / min.
[0086] Example 2 Example 2 provides a preparation process for silicon-carbon composite materials. The difference from Example 1 is that the lithium source content is adjusted. The specific process is as follows: Step S1 is the same as step S1 in Example 1.
[0087] In step S2, 2.25 kg of biphenyl and 27 kg of 1,2-dimethoxyethane were stirred and mixed for 2 hours. Then, under argon protection, 150 g of lithium sheets were added and stirred continuously for 12 hours until the lithium sheets were fully dissolved, resulting in a lithium-containing organic solution. The amount of lithium used was 1.5 times that in Example 1.
[0088] Step S3: Place the mesoporous carbon material in the deposition chamber of the deposition furnace, introduce argon gas into the deposition chamber to purge air, raise the temperature of the deposition furnace to 280°C, and use argon gas to carry the lithium-containing organic solution into the deposition furnace chamber. Maintain this temperature for 6 hours. The process is considered complete when all the lithium-containing organic solution has been introduced. The inert gas argon flow rate is 8 L / min, the inert carrier gas argon flow rate is 100 L / min, and the lithium-containing organic solution introduction rate is 75 mL / min.
[0089] Steps S4-S7 are the same as steps S4-S7 in Example 1.
[0090] Example 3 Example 3 provides a preparation process for silicon-carbon composite materials. The difference from Example 1 is that the lithium source content is adjusted. The specific process is as follows: Step S1 is the same as step S1 in Example 1.
[0091] In step S2, 0.75 kg of biphenyl and 9 kg of 1,2-dimethoxyethane were stirred and mixed for 2 hours. Then, under argon protection, 50 g of lithium flakes were added and stirred continuously for 12 hours until the lithium flakes were fully dissolved, resulting in a lithium-containing organic solution. The amount of lithium used was 0.5 times that in Example 1.
[0092] Step S3: Place the mesoporous carbon material in the deposition chamber of the deposition furnace, introduce argon gas into the deposition chamber to purge air, raise the temperature of the deposition furnace to 280°C, and use argon gas to carry the lithium-containing organic solution into the deposition furnace chamber. Maintain this temperature for 6 hours. The process is considered complete when all the lithium-containing organic solution has been introduced. The inert gas argon flow rate is 8 L / min, the inert carrier gas argon flow rate is 100 L / min, and the lithium-containing organic solution introduction rate is 25 mL / min.
[0093] Steps S4-S7 are the same as steps S4-S7 in Example 1.
[0094] Example 4 This embodiment 4 provides a process for preparing a silicon-carbon composite material. The difference from embodiment 1 is that the number of alternating deposition steps is increased in step S6. The specific process is as follows: Steps S1-S5 are the same as steps S1-S5 in Example 1.
[0095] Step S6: Repeat steps S4 and S5 five times, and then execute step S4 one more time. Specifically, execute step S4 → step S5 → step S4 → step S5 → step S4 → step S5 → step S4 → step S5 → step S4 → step S5 → step S4 → step S5 → step S4 to obtain the precursor material.
[0096] Step S7 is the same as step S7 in Example 1.
[0097] Example 5 This embodiment 5 provides a process for preparing a silicon-carbon composite material. The difference from embodiment 1 is that the number of alternating deposition steps is reduced in step S6. The specific process is as follows: Steps S1-S5 are the same as steps S1-S5 in Example 1.
[0098] Step S6: Repeat steps S4 and S5 once, and finally execute step S4 one more time. Specifically, execute step S4 → step S5 → step S4 in sequence to obtain the precursor material.
[0099] Step S7 is the same as step S7 in Example 1.
[0100] Example 6 This embodiment 6 provides a process for preparing a silicon-carbon composite material. The difference from embodiment 1 is that the germanium deposition time is adjusted in step S5. The specific process is as follows: Steps S1-S4 are the same as steps S1-S4 in Example 1.
[0101] Step S5: Adjust the temperature of the deposition furnace to 340℃, and introduce germane into the deposition chamber using argon gas. Maintain the temperature for 1 hour to allow the germanium produced by the pyrolysis of germane to deposit in the pores of the mesoporous carbon material. The inert carrier gas argon flow rate is 56 L / min, and the silane flow rate is 4 L / min. The germanium deposition time is twice that of Example 1.
[0102] Steps S6-S7 are the same as steps S6-S7 in Example 1.
[0103] Example 7 This embodiment 7 provides a preparation process for a silicon-carbon composite material. The difference from embodiment 1 is that in step S7, an impregnation-carbonization method is used to prepare a carbon coating layer. The specific process is as follows: Steps S1-S6 are the same as steps S1-S6 in Example 1.
[0104] Step S7: The precursor material is immersed in a 10wt% sucrose solution for 4 hours, then dried and carbonized at 630°C for 2 hours under an argon atmosphere to form a carbon coating layer on the outer surface of the precursor material, thus obtaining a silicon-carbon composite material.
[0105] Comparative Example 1 Comparative Example 1 provides a preparation process for a silicon-carbon composite material, which does not involve germanium deposition. The specific process is as follows: Steps S1-S3 are the same as steps S1-S3 in Example 1.
[0106] In step S4, argon gas is introduced into the deposition chamber for purging. Then, the temperature of the deposition furnace is raised to 440℃, and silane is introduced into the deposition chamber via the argon gas. The chamber is held at this temperature for 2 hours, allowing the silicon produced by the pyrolysis of silane to be uniformly deposited in the pores of the mesoporous carbon material. The flow rate of the inert argon gas is 8 L / min, the flow rate of the inert carrier argon gas is 56 L / min, and the flow rate of the silane is 4 L / min.
[0107] In step S5, the temperature of the deposition furnace is adjusted to 340℃, and only argon gas is introduced for heat preservation for 0.5 hours, without introducing germane. The flow rate of the inert carrier gas argon is 56 L / min.
[0108] Step S6: Repeat steps S4 and S5 three times, and then execute step S4 one more time. Specifically, execute step S4 → step S5 → step S4 → step S5 → step S4 → step S5 → step S4 to obtain the precursor material.
[0109] Step S7 is the same as step S7 in Example 1.
[0110] Comparative Example 2 Comparative Example 2 provides a preparation process for a silicon-carbon composite material. This Comparative Example 2 does not involve pre-lithiation. The specific process is as follows: Step S1 is the same as step S1 in Example 1.
[0111] In step S2, 1.5 kg of biphenyl and 18 kg of 1,2-dimethoxyethane are stirred and mixed for 2 h to obtain a lithium-free organic solution.
[0112] Step S3: Place the mesoporous carbon material in the deposition chamber, introduce argon gas into the chamber to purge air, raise the temperature of the deposition furnace to 280°C, and use argon gas to carry the lithium-free organic solution into the deposition furnace chamber. Maintain this temperature for 6 hours. The process is considered complete when all the lithium-free organic solution has been introduced. The inert argon gas flow rate is 8 L / min, the inert carrier argon gas flow rate is 100 L / min, and the lithium-containing organic solution introduction rate is 50 mL / min.
[0113] Steps S4-S7 are the same as steps S4-S7 in Example 1.
[0114] Comparative Example 3 Comparative Example 3 provides a process for preparing a silicon-carbon composite material. This Comparative Example 3 does not involve pre-lithiation or germanium deposition. The specific process is as follows: Step S1 is the same as step S1 in Example 1.
[0115] In step S2, 1.5 kg of biphenyl and 18 kg of 1,2-dimethoxyethane are stirred and mixed for 2 h to obtain a lithium-free organic solution.
[0116] Step S3: Place the mesoporous carbon material in the deposition chamber of the deposition furnace, introduce argon gas into the deposition chamber to purge air, raise the temperature of the deposition furnace to 280°C, and use argon gas to carry the lithium-free organic solution into the deposition furnace chamber. Maintain this temperature for 6 hours. The process is considered complete when all the lithium-free organic solution has been introduced. The inert argon gas flow rate is 8 L / min, the inert carrier argon gas flow rate is 100 L / min, and the lithium-containing organic solution introduction rate is 50 mL / min.
[0117] Step S4: Argon gas is introduced into the deposition chamber for purging, raising the temperature of the deposition furnace to 440℃. The argon gas carries the silane into the deposition chamber, and the chamber is held at this temperature for 2 hours. This allows the silicon produced by the pyrolysis of the silane to be uniformly deposited in the pores of the mesoporous carbon material, yielding the precursor material. The inert argon gas flow rate is 8 L / min, the inert carrier argon gas flow rate is 56 L / min, and the silane gas flow rate is 4 L / min.
[0118] In step S5, the temperature of the deposition furnace is adjusted to 340℃, and only argon gas is introduced for heat preservation for 0.5 hours without introducing germane, so that the mesoporous carbon material undergoes the same temperature and gas-phase heat treatment process as in step S5 of Example 1. The inert carrier gas argon gas flow rate is 56 L / min. In step S4, the temperature of the deposition furnace is raised to 580℃ under an argon atmosphere. Then, propylene is introduced along with the argon gas at a flow rate of 1L / min, and the temperature is maintained for 1 hour to form a carbon coating layer on the outer surface of the precursor material, ultimately obtaining a silicon-carbon composite material. The inert carrier gas argon gas flow rate is 50L / min.
[0119] Comparative Example 4 Comparative Example 4 provides a preparation process for a silicon-carbon composite material, which includes a post-pre-lithiation step. The specific process is as follows: Step S1 is the same as step S1 in Example 1.
[0120] In step S2, 1.5 kg of biphenyl and 18 kg of 1,2-dimethoxyethane are stirred and mixed for 2 h to obtain a lithium-free organic solution.
[0121] Step S3: Place the mesoporous carbon material in the deposition chamber of the deposition furnace, introduce argon gas into the deposition chamber to purge air, raise the temperature of the deposition furnace to 280°C, and use argon gas to carry the lithium-free organic solution into the deposition furnace chamber. Maintain this temperature for 6 hours. The process is considered complete when all the lithium-free organic solution has been introduced. The inert argon gas flow rate is 8 L / min, the inert carrier argon gas flow rate is 100 L / min, and the lithium-containing organic solution introduction rate is 50 mL / min.
[0122] Steps S4-S6 are the same as steps S4-S6 in the embodiment.
[0123] Step S7: The precursor material is placed in the deposition chamber of the deposition furnace. Argon gas is introduced into the deposition chamber to purge air. The temperature of the deposition furnace is raised to 280°C. The lithium-containing organic solution is carried into the deposition furnace chamber by the argon gas. The temperature is maintained for 6 hours. The process is considered complete when all the lithium-containing organic solution has been introduced, yielding the precursor material for post-lithiation supplementation. The inert argon gas flow rate is 8 L / min, the inert carrier argon gas flow rate is 100 L / min, and the lithium-containing organic solution introduction rate is 50 mL / min.
[0124] In step S8, the temperature of the deposition furnace is raised to 580°C under an argon atmosphere. Then, propylene with a flow rate of 1 L / min is introduced along with the argon gas, and the temperature is maintained for 1 hour. This allows a carbon coating layer to form on the outer surface of the precursor material for subsequent lithium supplementation, ultimately yielding a silicon-carbon composite material. The inert carrier gas argon gas flow rate is 50 L / min.
[0125] Comparative Example 5 Comparative Example 5 provides a process for preparing a silicon-carbon composite material, which does not involve silicon deposition. The specific process is as follows: Steps S1-S3 are the same as steps S1-S3 in Example 1.
[0126] In step S4, argon gas is introduced into the deposition chamber for purging. Then, the temperature of the deposition furnace is raised to 440°C, and argon gas is introduced only for 0.5 hours without introducing silane. The flow rate of the inert argon gas is 8 L / min, and the flow rate of the inert carrier argon gas is 56 L / min.
[0127] In step S5, argon gas is introduced into the deposition chamber for purging. Then, the temperature of the deposition furnace is adjusted to 340℃. Argon gas is used to carry germanane into the deposition chamber, and the chamber is held at this temperature for 0.5 hours. This allows the germanium produced by the pyrolysis of germanane to be uniformly deposited in the pores of the mesoporous carbon material, yielding the precursor material. The inert carrier gas argon flow rate is 56 L / min, and the germanane flow rate is 4 L / min.
[0128] Step S6: Repeat steps S4 and S5 three times, and then execute step S4 one more time. Specifically, execute step S4 → step S5 → step S4 → step S5 → step S4 → step S5 → step S4 to obtain the precursor material.
[0129] Step S7 is the same as step S7 in Example 1.
[0130] The negative electrode sheet was prepared using the materials prepared in this embodiment and the comparative example, and assembled into coin cell half-cells and full cells for testing. All test results are recorded in Table 1. The specific process is as follows: Assembly process of button cell: The silicon-carbon composite material, carbon black, and binder were weighed according to a mass ratio of 8:1:1; the binder was sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:0.8. A slurry was prepared using a pulping machine at room temperature. The prepared slurry was uniformly coated onto copper foil to a thickness of 220 μm, and dried in a forced-air drying oven at 55°C for 2 hours. The coated foil was then cut into circular electrode sheets with a diameter of 14 mm and vacuum-dried in a vacuum drying oven at 100°C for 8 hours. The dried electrode sheets were then immediately transferred to a glove box for later use.
[0131] Assembly of button cell batteries: The experiment was conducted in a glove box containing a high-purity argon atmosphere. Lithium metal was used as the counter electrode, and the electrolyte was a 1 mol / L LiPF6 solution. The solvent of the electrolyte was ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1. A polyethylene (PE) membrane was used as the separator, and the cells were assembled into a CR2032 coin cell.
[0132] Discharge specific capacity and initial coulombic efficiency at 0.8V: After the assembled CR2032 button cell was left to stand for 8 hours, it was placed on the Blue Electric Test System CT2001A at room temperature. It was first discharged at a constant current rate of 0.1C to 0.005V, and then charged at a constant current rate of 0.1C with a cutoff voltage of 2V. The initial discharge capacity (mAh) and the cumulative capacity (mAh) when the voltage reached 0.8V during the charging process were recorded. This cumulative capacity was recorded as the 0.8V reversible capacity.
[0133] The discharge specific capacity (mAh / g) is calculated using the following formula: Discharge specific capacity = Initial discharge capacity / Mass of silicon-carbon composite material on the electrode The unit for the mass of silicon-carbon composite materials is g.
[0134] The initial coulombic efficiency (%) at 0.8V is calculated using the following formula: 0.8V initial coulombic efficiency = 0.8V reversible capacity / initial discharge capacity × 100%.
[0135] At least three parallel coin cells were assembled for each sample for testing, and the average value was taken.
[0136] Ratio performance test: After the assembled CR2032 coin cell was allowed to stand for 12 hours to reach electrochemical equilibrium, constant current charge-discharge tests were performed at room temperature using a Blue Electric CT2001A testing system, with a test voltage range of 0.005V-2.0V. Specifically, five cycles of constant current charge-discharge tests were performed sequentially at 0.1C, 0.5C, 1C, 2C, and 3C rates, with a 5-minute rest period after each rate cycle. The average discharge specific capacity of the last three cycles at each rate was taken as the discharge specific capacity at that rate, and the 3C / 0.1C rate ratio was calculated to evaluate the rate performance of the material.
[0137] Full battery assembly process: Silicon-carbon composite material is mixed with graphite with a specific capacity of 350 mAh / g to form a composite anode material with a theoretical capacity of 520 mAh / g.
[0138] The obtained composite negative electrode material was assembled into a 5085-type small soft-pack all-electric battery for electrochemical performance testing. The composite negative electrode material, conductive agent Super P, carboxymethyl cellulose, and styrene-butadiene rubber were mixed and ground into a slurry at a mass ratio of 94.5:2:2:1.5, and then coated onto copper foil to prepare the negative electrode sheet. 811-type high-nickel ternary material, Super P, single-walled carbon nanotubes, and polyvinylidene fluoride were mixed and ground into a slurry at a mass ratio of 95.2:1.8:1:2, and then coated onto aluminum foil to prepare the positive electrode sheet. A 5085-type small soft-pack battery was assembled with 11 negative electrode sheets and 10 positive electrode sheets. The electrolyte was 1 mol / L LiPF6, with the solvent being EC, DMC, and DEC in a volume ratio of 1:1:1.
[0139] Cyclic performance test: The assembled 5085-type small pouch battery was placed on the Blue Electric testing system and subjected to constant current charge-discharge testing within a voltage range of 2.75-4.25V. The battery was first formed at a rate of 0.05C, then calibrated at a rate of 0.1C to determine its initial capacity, and then subjected to a 500-cycle test at a rate of 1C. The ratio of the discharge specific capacity at the 800th cycle to that at the 1st cycle was recorded as the 800-cycle retention rate.
[0140] Silicon grain size testing: Phase analysis of silicon-carbon composite materials was performed using X-ray diffraction (XRD) with a scanning range of 10°–80° and a scanning rate of 2° / min. The grain size of silicon was calculated based on the Scherrer formula D = Kλ / (β·cosθ), where K is the Scherrer constant (0.89), λ is the X-ray wavelength (Cu target, λ = 0.15406 nm), β is the full width at half maximum (FWHM, in radians) of the diffraction peak on the silicon (111) plane, and θ is the diffraction angle.
[0141] Table 1 As can be seen from the data in Table 1, the silicon-carbon composite materials prepared in each embodiment of the present invention exhibit excellent electrochemical performance. The discharge specific capacity, initial coulombic efficiency at 0.8V, 3C / 0.1C rate ratio, and 800-cycle retention rate of each embodiment are all at high levels, and the silicon grain size is also effectively refined. These results demonstrate that the present invention successfully constructs silicon-carbon composite materials with alternating silicon-germanium sandwich structures through a pre-lithiation-alternating vapor deposition silicon / germanium-carbon coating process, and the comprehensive electrochemical performance of each embodiment is excellent.
[0142] The effects of pre-lithiation, germanium deposition, silicon-germanium alternating sandwich structure, and carbon coating on material properties are discussed below: First, the impact of pre-lithiation method on electrochemical performance.
[0143] Comparing Example 1 and Comparative Example 2, both underwent germanium deposition and formed alternating silicon-germanium sandwich structures. The difference lies in that Example 1 employed pre-lithiation, while Comparative Example 2 did not. Under similar discharge specific capacities, Example 1 exhibited significantly better initial coulombic efficiency at 0.8V and 800-cycle retention than Comparative Example 2. This indicates that pre-lithiation allows lithium particles to be uniformly attached to the inner pore walls of the mesoporous carbon material beforehand. Subsequently, the nano-silicon and nano-germanium particles generated by vapor deposition can undergo in-situ alloying reactions with the pre-placed lithium particles within the pores, achieving uniform distribution and efficient utilization of lithium at the molecular scale, thereby effectively improving the initial coulombic efficiency and cycle stability of the material.
[0144] Comparing Example 1 and Comparative Example 3, it can be seen that Comparative Example 3, which has neither pre-lithiation treatment nor germanium deposition, has significantly lower initial coulombic efficiency at 0.8V and 800-cycle retention rate than Example 1, and its silicon grain size is also significantly larger than that of Example 1. This indicates that the introduction of pre-lithiation and germanium deposition improves the initial coulombic efficiency and cycle stability of the material.
[0145] As can be seen from Examples 1-3, the initial coulombic efficiency at 0.8V gradually increases with the increase of lithium content, indicating that the initial coulombic efficiency of the material can be effectively controlled by adjusting the amount of lithium-containing organic solution, thus verifying the adjustability of the lithium source pre-processing scheme in this invention.
[0146] Comparing Example 1 and Comparative Example 4, it can be seen that the initial coulombic efficiency at 0.8V and the 800-cycle retention rate of Comparative Example 4 are both lower than those of Example 1. This indicates that during post-pre-lithiation, lithium elements are mainly distributed on the surface of the material and are difficult to fully penetrate into the internal pores of the mesoporous carbon material to form an effective alloy with the nano-silicon particles, resulting in low pre-lithiation efficiency. In contrast, the pre-pre-lithiation scheme of the present invention has significant advantages.
[0147] Second, the impact of germanium deposition on rate performance and silicon grain size.
[0148] Comparing Example 1 and Comparative Example 1, both underwent pre-lithiation treatment. The difference lies in that Example 1 performed germanium deposition after silicon deposition, forming a silicon-germanium alternating sandwich structure, while Comparative Example 1 only performed silicon deposition without germanium deposition. Example 1 exhibited a better 3C / 0.1C rate capability than Comparative Example 1, and its silicon grain size was smaller. This indicates that the introduction of germanium effectively refines the silicon grain size, while simultaneously utilizing germanium's high electronic conductivity to improve the material's rate performance.
[0149] Comparing Examples 4 and 5, it is evident that increasing the number of alternating deposition cycles improves both the 3C / 0.1C rate ratio and the 800-cycle retention rate, and further refines the silicon grain size, compared to decreasing the number of alternating deposition cycles. This indicates that increasing the number of silicon-germanium alternating deposition cycles is beneficial for further optimizing the rate performance and cycling characteristics of the material.
[0150] Comparing Examples 1 and 6, it can be seen that increasing the germanium deposition amount improves the rate performance, but decreases the discharge specific capacity. This indicates that an appropriate amount of germanium introduction is beneficial to improving rate performance, but excessive germanium will reduce the content of active silicon, leading to a decrease in specific capacity.
[0151] Third, the influence of silicon-germanium alternating sandwich structure on electrochemical performance.
[0152] Comparing Example 1 and Comparative Example 5, it can be seen that Comparative Example 5 only performed germanium deposition without silicon deposition, and its initial coulombic efficiency at 0.8V, 3C / 0.1C rate ratio, and 800-cycle retention rate are all significantly lower than those of Example 1. This indicates that germanium alone cannot provide a sufficiently high lithium storage capacity, and silicon is indispensable as the main active material. The silicon-germanium alternating sandwich structure achieves synergistic optimization of capacity and rate performance by combining high-capacity silicon with highly conductive germanium at the nanoscale.
[0153] Comparing the silicon grain size data of each embodiment and the comparative examples, it can be seen that the silicon grain size of each embodiment of the present invention is smaller than that of Comparative Examples 1 and 3 without germanium deposition, and also smaller than that of Comparative Example 2 without pre-lithiation. The reduction in silicon grain size effectively alleviates the volume expansion stress during charging and discharging, thereby improving the cycle stability of the material.
[0154] Fourth, the effect of carbon coating method on electrochemical performance.
[0155] Comparing Examples 1 and 7, it can be seen that the silicon-carbon composite materials prepared by the two carbon coating methods, CVD carbon coating and impregnation-carbonization carbon coating, are quite similar in terms of discharge specific capacity, 0.8V initial coulombic efficiency, 3C / 0.1C rate ratio, and 800-cycle retention rate. This indicates that the two carbon coating methods provided by the present invention can achieve good surface coating effect, effectively reduce irreversible capacity loss, and improve the cycling stability of the material.
[0156] In summary, the data in Table 1 fully validates that the silicon-carbon composite material prepared by this invention, through a process route of pre-lithiation followed by alternating vapor deposition of silicon / germanium-carbon coating, exhibits comprehensive superior performance, including high discharge specific capacity, high initial coulombic efficiency, excellent rate performance, and long cycle life. This stems from the design of this invention: the mesoporous carbon material provides ample lithium storage space and an ion conduction network; pre-lithiation achieves uniform lithium distribution within the pores, compensating for the irreversible capacity loss caused by SEI formation and improving the initial coulombic efficiency; the alternating silicon-germanium sandwich structure effectively reduces the size of silicon grains, improving material expansion performance while enhancing rate performance; and the outermost carbon coating layer further stabilizes the electrode / electrolyte interface. The synergistic effect of these multiple structures enables the silicon-carbon composite material prepared by this invention to simultaneously meet the application requirements of high capacity, high initial efficiency, high rate performance, and long cycle life when applied to the anode of lithium-ion batteries.
[0157] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A silicon-carbon composite material, characterized in that, The silicon-carbon composite material includes: Mesoporous carbon materials; Lithium particles are uniformly attached to the inner pore walls of the mesoporous carbon material. Nano-silicon particles are obtained by vapor deposition in the pores of the mesoporous carbon material. Germanium nanoparticles were obtained by vapor deposition in the pores of the mesoporous carbon material. Lithium-silicon alloy particles and / or lithium-germanium alloy particles and / or lithium-silicon-germanium alloy particles are located inside the pores of the mesoporous carbon material; Silicon-germanium alloy particles are located inside the mesoporous carbon material and are generated by in-situ alloying reaction between the nano-silicon particles and the nano-germanium particles at the interface. A carbon coating layer is applied to the outer surface of the mesoporous carbon material. The lithium particles are obtained by vaporizing a lithium-containing organic solution and adsorbing it into the pores of the mesoporous carbon material, followed by pyrolysis. Some of the lithium particles undergo an in-situ alloying reaction with some of the nano-silicon particles and / or some of the nano-germanium particles generated by subsequent vapor deposition to generate lithium-silicon alloy particles and / or lithium-germanium alloy particles and / or lithium-silicon-germanium alloy particles. In the pores of the mesoporous carbon material, nano-silicon layers formed by the aggregation of nano-silicon particles and nano-germanium layers formed by the aggregation of nano-germanium particles are arranged alternately to form a silicon-germanium alternating sandwich structure; silicon-germanium alloy particles are present at the interface between the nano-silicon layers and the nano-germanium layers.
2. The silicon-carbon composite material according to claim 1, characterized in that, The mesoporous carbon material has a mesoporous rate of 50%-95%; a pore size of 0.2 nm-10 nm; and a pore volume of 0.6 cm³. 3 / g-1.2cm 3 / g; the specific surface area of the mesoporous carbon material is 110m². 2 / g-2000m 2 / g.
3. The silicon-carbon composite material according to claim 1, characterized in that, The specific surface area of the silicon-carbon composite material is 1 m². 2 / g-10m 2 / g; the particle size D50 of the silicon-carbon composite material is 3μm-15μm.
4. A method for preparing a silicon-carbon composite material as described in any one of claims 1-3, characterized in that, The preparation method includes: Step S1: Mix the carbon precursor and the pore-forming agent in a certain proportion, and perform carbonization treatment under a protective atmosphere to obtain a carbonized precursor. Then, remove the residual pore-forming agent and its by-products in the carbonized precursor by acid washing and water washing until the solution is neutral. Finally, dry the precursor to obtain a mesoporous carbon material. Step S2: Lithium metal is placed in an organic solution under a protective atmosphere and stirred continuously until fully dissolved to obtain a lithium-containing organic solution; the organic solution includes an organic solvent and a co-solvent, and during the stirring process, the lithium metal combines with part of the co-solvent to form a lithium-co-solvent complex; Step S3: Place the mesoporous carbon material in the deposition chamber of the deposition furnace, introduce inert gas into the deposition chamber to expel air, heat the deposition furnace to the first deposition temperature, and introduce the lithium-containing organic solution into the deposition chamber through the inert carrier gas. The lithium-containing organic solution forms mist droplets. As the organic solvent in the mist droplets evaporates, the lithium-cosolvent complex and the remaining cosolvent in the lithium-containing organic solution are uniformly attached to the inner pore wall of the mesoporous carbon material. Step S4: Inert gas is introduced into the deposition chamber for purging to remove residual organic solvents and their pyrolysis products, as well as the remaining co-solvent. Subsequently, the deposition furnace is heated to the second deposition temperature, causing the lithium-co-solvent complex adhering to the inner wall of the pores to thermally decompose and release lithium particles. Then, the chamber temperature is maintained at the second deposition temperature, and silicon source gas is introduced into the deposition chamber through an inert carrier gas and kept at the temperature, so that the silicon generated by the pyrolysis of the silicon source gas is deposited in the pores of the mesoporous carbon material, growing to form nano-silicon particles. At the same time, some of the nano-silicon particles undergo an in-situ alloying reaction with some of the lithium particles to generate lithium-silicon alloy particles. Step S5: Adjust the temperature of the deposition furnace to the third deposition temperature, introduce germanium source gas into the deposition chamber using an inert carrier gas and keep it at the temperature, so that the germanium produced by the pyrolysis of the germanium source gas is deposited in the pores of the mesoporous carbon material, growing to form nano-germanium particles; simultaneously, some of the nano-germanium particles undergo an in-situ alloying reaction with some of the lithium particles to generate lithium-germanium alloy particles; furthermore, some of the nano-germanium particles undergo an in-situ alloying reaction with the lithium-silicon alloy particles to generate lithium-silicon-germanium alloy particles. Step S6: Repeat steps S4 and S5 for a total of N times, and then execute step S4 one more time. In the pores of the mesoporous carbon material, a silicon-germanium alternating sandwich structure is formed, in which nano-silicon layers formed by the aggregation of nano-silicon particles and nano-germanium layers formed by the aggregation of nano-germanium particles are alternately arranged, and silicon-germanium alloy particles are formed at the interface between the nano-silicon layers and the nano-germanium layers, thus obtaining the precursor material; wherein, N≥2. Step S7: Carbon coating treatment is performed on the precursor material to form a carbon coating layer on the outer surface of the precursor material, thereby obtaining a silicon-carbon composite material.
5. The preparation method according to claim 4, characterized in that, The carbon precursor includes a carbon-containing polymer, which includes one or more of glucose, sucrose, starch, polyvinylpyrrolidone, polyvinylidene fluoride, phenolic resin, polyvinyl chloride, or cellulose. The pore-forming agent includes one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, or sodium sulfate; The lithium metal includes one or more of lithium sheets, lithium blocks, or lithium powder; The organic solvent includes one or more of 1,2-dimethoxyethane, tetrahydrofuran, diethyl ether, dioxolane, dimethyl sulfoxide, or dimethylformamide; the co-solvent is an aromatic hydrocarbon compound, including one or more of biphenyl or naphthalene. The protective atmosphere includes one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The inert gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The inert carrier gas includes one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The silicon source gas includes one or more of silanes or chlorosilanes; The germanium source gas includes one or more of germane, digermane, or propargane. The carbon source gas includes one or more of methane, ethane, propane, or acetylene.
6. The preparation method according to claim 4, characterized in that, The mass ratio of the carbon precursor to the pore-forming agent is 1:1 to 1:5; The mass ratio of the mesoporous carbon material to the lithium-containing organic solution is 100:1-100:5; The lithium concentration in the lithium-containing organic solution is 0.1wt%-0.3wt%; The flow rate of the lithium-containing organic solution is 10 mL / min-40 mL / min; The flow rate of the inert gas is 2L / min-10L / min; The flow rate of the inert carrier gas is 50L / min-125L / min; The flow rate of the silicon source gas is 4L / min-20L / min; The flow rate of the germanium source gas is 4L / min-20L / min.
7. The preparation method according to claim 4, characterized in that, The carbonization treatment temperature is 700℃-1300℃, and the carbonization treatment time is 1h-4h; The drying temperature is 50℃-130℃, and the drying time is 3h-15h; The first deposition temperature is 80℃-360℃, and the holding time is 200min-800min; The second deposition temperature is 400℃-500℃, and the holding time is 1h-36h; The third deposition temperature is 300℃-400℃, and the holding time is 1h-36h.
8. The preparation method according to claim 4, characterized in that, The carbon coating process includes: The precursor material is placed in a reactor, heated to 500℃-750℃ under a protective atmosphere, and then subjected to chemical vapor deposition (CVD) for 1-4 hours by introducing a carbon source gas; or... The precursor material is immersed in a carbon precursor solution for 3-8 hours, then removed and dried, and then carbonized at 500-750°C for 1-4 hours under a protective atmosphere.
9. A negative electrode sheet, characterized in that, The negative electrode sheet comprises the silicon-carbon negative electrode material according to any one of claims 1-4, or the silicon-carbon negative electrode material prepared by any one of claims 5-8.
10. An energy storage device, characterized in that, The energy storage device includes: for lithium-ion batteries or lithium-ion capacitors; The energy storage device includes the silicon-carbon anode material according to any one of claims 1-4, or the silicon-carbon anode material prepared by any one of claims 5-8, or the silicon-carbon anode material according to claim 9.
Citation Information
Patent Citations
Pre-lithiated negative plate as well as preparation method and application thereof
CN112072078A
Pre-lithiated silicon-carbon negative electrode material, preparation method and application
CN118825229A
